Sambal Bilis Missbee pre-order system / Nur Hidayah Mohd Yusoff - Mohd Yusoff, Nur Hidayah (2023)
Sambal Bilis Missbee is a local retailer organization that provides ready-to-eat products. A few current problems happened in the current business process, such as the store has lack of Customer Relationship Management (CRM) which is sellers cannot respond quickly to every customer. This also makes the seller overlook the questions from regular or new customers. Then, the current platform service does not provide complete updates to customers to get information about their product status. The customer will only be able to know when the products are ready for delivery. From the current problem that exists, Sambal Bilis Missbee Pre-order System is being developed. The Sambal Bilis Missbee Pre-order system will be used as an asset for the Sambal Bilis Missbee to generate a profit. Through this system, customers can purchase Sambal Bilis Missbee products through the website, and Sambal Bilis Missbee can generate revenue through online sales. The system is developed by following the adapted waterfall model phases. The adapted waterfall model consists of six phases: planning, requirement analysis, design, development, testing, and documentation. Some design activities have been used during the design phases, such as Context Diagram, Data Flow Diagram (DFD), Entity Relationship Diagram (ERD), Site Map, and User Interface (UI). The Electronic Customer Relationship Management Theory (E-CRM) also has been used in developing the system. This theory is used on to design the system based on the consumer purchase behavior when using the system. The suitable feature in each dimension of the comparison will be used as a guideline in implementing the Sambal Bilis Missbee Pre-order system. The Sambal Bilis Missbee Pre-order system is solving the current problem faced by Sambal Bilis Missbee. The system requirement and user requirements are met by the system. Most functionality is a pass; the actual result is like the expected result. In the future, the Sambal Bilis Missbee Pre-order System will be upgraded to allow more ordering process been made by customers and generate more revenue to the Sambal Bilis Missbee.